2017
DOI: 10.24193/adn.10.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction Levels and Problem-Solving Skills in the Teaching Profession: An Investigation

Abstract: Abstract. In this research, the relationship between Internet addiction levels among teaching candidates and their problem-solving aptitude and self-efficacy perceptions towards the teaching profession was investigated. In addition, the effects of gender, department, Internet use and sporting habits on the Internet addiction, problem-solving skills and self-efficacy perceptions among teaching candidates were examined. The sample in this study comprised final-grade teaching candidates who were in the graduation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…These results are similar to those results of several studies (Wei, Russell, &Zakalik, 2005;Hermann, 2005;Erozkan & Deniz, 2012 ;Al Khatib, 2012 ;Carparo, 2014;Ibili, 2017;Afrin, 2016 ;Zeng, Ye, Hu & Ma, 2016 ;Feldman, Davidson, Ben-Naim, Maza, & Margalit, 2016) which indicate that there is a negative correlation between social self-efficacy, loneliness and internet addiction. However, Esen, Aktas and Tuncer(2013) concluded that there is no correlation between social self-efficacy and internet addiction.…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to those results of several studies (Wei, Russell, &Zakalik, 2005;Hermann, 2005;Erozkan & Deniz, 2012 ;Al Khatib, 2012 ;Carparo, 2014;Ibili, 2017;Afrin, 2016 ;Zeng, Ye, Hu & Ma, 2016 ;Feldman, Davidson, Ben-Naim, Maza, & Margalit, 2016) which indicate that there is a negative correlation between social self-efficacy, loneliness and internet addiction. However, Esen, Aktas and Tuncer(2013) concluded that there is no correlation between social self-efficacy and internet addiction.…”
Section: Discussionsupporting
confidence: 91%
“…In general, the higher the smartphone addiction tendency, the lower the problem-solving ability will be. Similar findings have shown that addiction tendencies are negatively correlated with problem-solving and critical thinking skills (İbili, 2017;Lee & Kim, 2017).…”
Section: Relations Between Variablessupporting
confidence: 62%
“…Obstacles and conflicts can prevent an individual from reaching one’s goals. Novel problems such as new jobs as well as novel tasks and goals can be managed with effective problem-solving skills in an uncertain and complex society and positive results can be obtained with problem-solving mechanisms, and choosing an effective solution among possible or alternative solutions ( 16 ). Making logical decisions and carrying out activities should be in accordance with goals and objectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Making logical decisions and carrying out activities should be in accordance with goals and objectives. Problem-solving skills depend on an individual’s experience and rational problem-solving skills can be effective as a positive orientation toward problem solving ( 16 , 17 ). Trial-and-error and internal or causal approaches are applied to find solutions to problems.…”
Section: Literature Reviewmentioning
confidence: 99%